STUDI HABITAT DAN KEBIASAAN MAKANAN (FOOD HABIT) IKAN RONO LINDU (Oryzias sarasinorum POPTA, 1905) - Gani, Abdul (JSTT, 2015)
The ricefish Sasarin’s buntingi (Oryzias sarasinorum Popta, 1905), known locally as rono Lindu, has an endemic distribution limited to Lindu Lake, Central Sulawesi, Indonesia. This species is increasingly rare and has been listed as Endangered in the IUCN Red List since 1996. The goals of this research were to analyse and describe the habitat and food habit of rono Lindu. The study covered four months, from September to December 2015. Rono Lindu habitat was categorized based on three substrate types: sand, sandy silt, and silt. The sampling stations were as follows: sandy habitat site named Kalanci, in Langko Village; sandy silt habitat site named Lovu in Anca Village and silty habitat site named Tomado. At all three stations rono Lindu growth patterns were allometric negative, with length increasing faster than weight. Condition factor values were indicative of relatively narrow bodied, slim rather than fat fish. Rono Lindu can be categorised as stenophagic, with relatively few diet components. Diet was dominated by phytoplankton at all three sites, with four species identified as Melosira sp., Synedra sp., Rhizosolenia and Thalassionema nitzschionides. The most common of these was Melosira sp., with the highest observed gut content proportion (58.31%) at the sandy substrate site. The abundance of rono Lindu food available varied between the sand, sandy silt and silty substrates, and rono Lindu have to compete for these resources with alien fish species introduced to Lindu Lake.